2013
DOI: 10.1099/mic.0.066050-0
|View full text |Cite
|
Sign up to set email alerts
|

ompW is cooperatively upregulated by MarA and SoxS in response to menadione

Abstract: OmpW is a minor porin whose biological function has not been clearly defined. Evidence obtained in our laboratory indicates that in Salmonella enterica serovar Typhimurium the expression of OmpW is activated by SoxS upon exposure to paraquat and it is required for resistance. SoxS belongs to the AraC family of transcriptional regulators, like MarA and Rob. Due to their high structural similarity, the genes under their control have been grouped in the mar/sox/rob regulon, which presents a DNA-binding consensus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…We next tested whether measurable lycopene content could be decreased by high levels of intracellular ROS. Therefore, the high lycopene producer Seq + was treated with menadione, which induces ROS formation in E. coli [ 47 , 48 ]. The measurable lycopene content decreased significantly in the presence of sublethal doses of menadione (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next tested whether measurable lycopene content could be decreased by high levels of intracellular ROS. Therefore, the high lycopene producer Seq + was treated with menadione, which induces ROS formation in E. coli [ 47 , 48 ]. The measurable lycopene content decreased significantly in the presence of sublethal doses of menadione (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, deletion of marA did not affect the oral inoculation LD 50 values of Salmonella in mice [176]. Additionally, in WT strains, MarA and SoxS co-operatively induce the expression of ompW upon exposure of the bacteria to menadione [179]. OmpW is a minor immunogenic membrane porin that has been implicated in paraquat resistance, osmoprotection and hydrogen peroxide, and hypochlorous acid influx [179 and references therein].…”
Section: Homologs In Enterobacteriaceaementioning
confidence: 99%
“…Additionally, in WT strains, MarA and SoxS co-operatively induce the expression of ompW upon exposure of the bacteria to menadione [179]. OmpW is a minor immunogenic membrane porin that has been implicated in paraquat resistance, osmoprotection and hydrogen peroxide, and hypochlorous acid influx [179 and references therein]. OmpW has not been shown to be regulated by the TRs in E. coli , but other porins are under their control, suggesting a similar theme for both species (see section 5.2.2).…”
Section: Homologs In Enterobacteriaceaementioning
confidence: 99%
“…Another study showed that the synthesis of OmpA was decreased by visible irradiation [20]. A study of oxidative stress showed that the amount of OmpW protein was increased 1.7 fold when Salmonella typhimurium was treated with the superoxidegenerating agent menadione [23]. Chou et al (1993) also showed that micF transcription was strongly inducible, but wholly-dependent, on the soxRS locus in response to treatment with the superoxide-generating agent Paraquat [24].…”
Section: Resultsmentioning
confidence: 99%